Safety and Exposure Area in Three Different Posteromedial Surgical Approaches for the Treatment of Ankle Fractures. A Cadaveric Study - Jorge Filippi MD, MBA; Joaquin Palma MD; Sergio Morales MD, MSc; Tomas Urrutia MD (Foot & Ankle Orthopaedics)
Category: Ankle; Trauma Introduction/Purpose: Posterior malleolar fractures, are common in ankle injuries. Open reduction and internal fixation show better outcomes, particularly with direct reduction. While posterolateral fractures can be managed through a posterolateral approach, the optimal approach for large posterior and posteromedial fractures is uncertain. Different posteromedial approaches exist, but concerns persist about soft tissue dissection and posteromedial neurovascular bundle (NVB) safety. This study compares three posteromedial approaches — posteromedial (PM), Modified posteromedial (MoPM), and medial posteromedial (MePM) — measuring posterior malleolar visualization, distance to the neurovascular bundle, and tension. Results aim to compare them regarding bone exposure and safety to the posteromedial NVB. Methods: We used 12 cadaveric pieces and evaluated the following approaches: PM: longitudinal incision immediately parallel to the medial border of the Achilles tendon. The FHL fascia was opened and the FHL retracted laterally. MoPM longitudinal incision halfway between the posteromedial tibia's edge and the Achilles tendon's medial edge. The PTT was mobilized medially and the FDL laterally. MePM longitudinal incision along the posteromedial edge of the tibia. The i PTT tendon was retracted posteriorly and elevated Measurements included minimal tension on the posteromedial (NVB) flap, distance from the incision to the NVB, and percentage of malleolar exposure. Tension was gauged using a digital strain gauge on a Langenbeck retractor, while exposure was determined by marking bone edges and measuring medial-to-lateral length. Distribution of the data was assessed by the t-test. A one-way repeated measures ANOVA was conducted, when a significant difference was detected, the post hoc Tukey test was applied. Results: There were significant differences between the three approaches examined regarding the degree of posterior malleolar exposure and distance from the incision to the NBV, favoring the PM approach (71,00% ±1.83 and 25.50 mm ±4.20). The PM approach provided a significantly lower tension to the flap containing the posteromedial NVB (6.18 N ±1.28) compared to the other two approaches. Conclusion: The PM approach achieved the highest degree of posterior malleolar exposure, the lowest tension to the posteromedial NVB, and the greatest distance between the incision and the NBV. Thus, we believe it should be considered the approach of choice for large fractures of the posteromedial aspect of the PM.